Examining the Impact of COVID-19 on the Banking Industry: A Bibliometric Analysis - Aisyah As-Salafiyah; Aam Slamet Rusydiana (Journal of Business and Political Economy : Biannual Review of The Indonesian Economy, 2021)
The impact of COVID-19 on the banking industry has had a significant effect. This study tries to map the development of research published in this field. The research was conducted using VOSViewer software. The data analyzed in the form of scientific research related to the impact of COVID-19 on the banking industry totaling 28 articles indexed by the Scopus database. The results show that the number of research publications on the impact of COVID-19 on the banking industry is quite large. The network visualization shows that the map of developing research on the impact of COVID-19 on the banking industry is divided into several clusters with the most popular keywords, namely COVID-19, banking and viral disease. The top authors are Strongbayefa A, Akhmetov Y, Mohan T and Baskaran A, the top agencies are the Technical Expert Group on Sustainable Finance, Brussels and the Department of Accounting Finance, Rennes School of Business. The most popular countries are India, Canada and Saudi Arabia. Besides, it was found that research on the impact of COVID-19 on the banking industry was felt recently due to credit and non-performing loans which then had implications for restructuring policies. In the end, conventional banking is more affected by COVID-19 than Islamic banking in terms of its problematic financing ratio. Keywords: Banking Industry, Covid-19, Bibliometrics JEL Classification: G21, O16.